English Socio-Economic Impact Of People's Gold Mining For Farmers In Debowae Village, Waelata District, Buru District - Trisnawati Belen; August E Pattiselano; Junianita F sopamena (Cita konsultindo, 2023)
This research aims to determine the social and economic impact of gold mining on farmers in Debowae Village, Waelata District, Buru Regency. The type of research used in this research is qualitative, namely a method that focuses on solving problems that exist in the actual present, then the data that has been collected is first compiled, explained and analyzed. The results of this research show that the social impact of gold mining from the social aspect is: there has been a change in the orientation of farmers who realize the importance of children's education and a decline in social interaction between farmers which is reflected in the weakening of mutual cooperation activities . Meanwhile, the economic impact that occurred was the shift in jobs from farmers to gold prospectors, because the income opportunities from searching for gold were much higher. This causes agricultural businesses to decrease, and farmers have the opportunity to abandon them